Studi Implementasi Digital Marketing Pada Pengusaha Di Semarang - Maria Yosephine Dwi Hayu Agustini; Sentot Suciarto Athanasius; Berta Bekti Retnawati; Antonius Haryo Perwito; Dyah Titisari Anugraheni (Universitas Katolik Soegijapranata, Semarang, 2021)
The application of digital marketing is increasingly widespread and has been applied by many entrepreneurs as a strategy to enter or expand the market. Entrepreneurs can choose ways and forms of digital marketing that suit the characteristics of their businesses and consumers. This study is intended to determine how far the level of digital marketing implementation for entrepreneurs in the city and district of Semarang. The study used a sample of 30 entrepreneurs who had implemented digital marketing and were selected using convenient sampling. Data were collected by questionnaires that were delivered in person or by email and processed with descriptive statistics to be analyzed using descriptive methods. The results show that the implementation of digital marketing is quite high. This means that entrepreneurs have used digital facilities (internet) in all their marketing activities, which include the delivery of product and business information, product ordering facilities, delivery of payment method options and delivery services. In the future, research can be focused on understanding online buying behavior that can be utilized by entrepreneurs in determining the right marketing strategy.